EMPLOYEE PROFESSIONAL DEVELOPMENT OF SOCIAL SECURITY STAVROPOL TERRITORY: COMPETENCE APPROACH - Elena Zritneva (Вестник Северо-Кавказского федерального университета)
The problems of implementation of the competence-based approach in the training of employees of the social protection of the population of the Stavropol Territory. The experience of training of social workers in the Stavropol region. The results of the questionnaire to identify trainees self sformirovannnosti professional competencies. Identiied problems of implementation of competence approach to training courses. The author identified the need for a phased sequential training courses with mandatory fixing of practical skillsthe Stavropol Territory. The results of a questionnaire survey of students of the course.